The Relationship Of The Level Of Mother's Knowledge And Efforts To Prevent Upper Respiratory Tract Infectious Diseases In Children At Nuhon Health Center - Tawil, Muh. Risal; Damayanti, Yusnika; Ruagadi, Henry A. (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Acute Respiratory Infection is an acute infectious disease that attacks one or more parts of the respiratory tract from the nose (upper tract) to the alveoli (lower tract). The main transmission of upper respiratory tract infections is through droplets that come out of the sufferer's nose/mouth when coughing or sneezing which contain bacteria. Some cases of upper respiratory tract infections can cause extraordinary events with high mortality and morbidity rates, causing a public health emergency and becoming a national problem. This study used an analytical design with the aim of identifying the relationship between independent variables, namely maternal knowledge and prevention of the incidence of upper respiratory tract infections at the Nuhon Community Health Center. The sample used was 74 mothers. The results of the research found that 62 respondents (83.8%) had poor knowledge and 12 people had good knowledge (16.2%), it was found that 64 respondents (16.2%) were found. 86.5%) did it incorrectly and 10 people did it correctly (13.5%). The research conclusions show that from the test results of respondents and the incidence of Upper Respiratory Tract Infections , there is a relationship between overall knowledge and prevention efforts against Upper Respiratory Tract Infections.